Police organization and the policing of assemblies in Germany - Bürger, Bernd (Public Order Policing, 2024)
In this chapter we highlight some aspects of the German police organization and standards that matter when policing assemblies or large-scale events. Hereafter, we will show an example of how an assembly would be policed, using a fictitious case study in a fictitious city. Finally, we will provide a brief overview of cross-border police collaboration in Europe considering assembly or event situations.